(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Massive extraction of groundwater for boro rice is the main cause of declining groundwater tables, especially in Rangpur Division, which is now a burning issue at the national level. It is now scientifically proven that rice is not a water-loving plant, but rather a water-tolerant plant. AWD can save water and energy, where both farmers and pump-owners can save around 30% of their irrigation water requirements. In Bangladesh around 4.8 million hectares of land are brought under irrigated boro rice where AWD technology can be utilized. With introduction of AWD technology, a savings of electricity costs equivalent to 5 billion Tk. or fuel cost equivalent to 7 billion Tk. will be incurred at the national level. Hence, the implementation of AWD technology will have major impacts at the farm and national levels, which can reduce irrigation cost significantly, thus saving foreign currency, as well as reducing excessive use of ground water. J. Bangladesh Agril. Univ. 16(1): 1-4, April 2018